(untitled) (Nigerian Journal of Technology, 2021)
Wireless access technology is a popular means of delivering various telecommunication services to users in Nigeria. Wireless Mesh Networking and Wireless Sensor Networking have found useful applications in wireless access systems, surveillance and infrastructure Management. A key problem associated with this technology is performance degradation in terms of Quality of Service (QoS). Achieving good QoS in Wireless Networks design involves implementing a robust routing optimization technique. Genetic Algorithm (GA) technique in NS2 network simulator was used to implement routing optimization in order to solve the performance issues experienced in a campus-based Voice over Internet Protocol (VoIP) communication system. The Interference and Load Aware (ILA) routing metric was chosen as the fitness function which helps to select the best route from a set of identified traffic paths that best guarantees low delay, high throughput and low packet losses suitable for real time communication. Results show that the GA based route optimization produced a 23% improvement in Throughput, 11% less Delay and 16% less Packet loss in comparison to the non-GA route. This work shows that route optimization in wireless multi-hop networks based on GA and ILA improves its QoS.